Exposure to Olfactory Alcohol Cues During Non-rapid Eye Movement Sleep Did Not Decrease Craving in Patients With Alcohol Dependence - Zhu, Ran; Ni, Zhaojun; Tao, Ran; Cheng, Jun; Pang, Liangjun; Zhang, Shun; Zhang, Yang; Xue, Yanxue; Ma, Yundong; Sun, Wei; Lu, Lin; Deng, Jiahui; et al. (Frontiers in Psychiatry, 2022)
Background and objectives: Cue exposure therapy (CET) has been used to reduce alcohol use, but the effect of CET during sleep on alcohol dependence (AD) is unclear. The present study examined the effect of repeated exposure to an olfactory stimulus during non-rapid eye movement (NREM) sleep on cue reactivity and craving in patients with AD. Methods: Thirty-five patients with AD were enrolled according to the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-Ⅳ). All the subjects were randomly assigned to the experimental or control group. The experimental group was exposed to alcohol odor for 10 min during NREM sleep. The other group (controls) was exposed to water (control stimulus, CtrS) for 10 min during NREM sleep. Demographic, alcohol-related, and clinical characteristics were collected at baseline. A cue-reactivity test was conducted before and after exposure to evaluate the effect of memory manipulation on acute response to an alcohol stimulus. Results: There were no significant time × group interactions according to the visual analog scale (VAS) score of craving intensity, skin conductance response (SCR), systolic blood pressure (SBP), and diastolic blood pressure (DBP; all p > 0.05). Two-way ANOVA showed significant main effects of time on SCR (F (1,33) = 4.453, p < 0.043), SBP (F (1,33) = 14.532, p = 0.001), DBP (F (1,33) = 8.327, p = 0.007), Craving-VAS (F (1,33) = 1.997, p = 0.167) in two groups. Conclusions: Exposure to olfactory alcohol cues during NREM sleep had no significant effect on alcohol craving in subjects with AD during hospitalization.